Correction: Zhou et al. Integrating Chinese Herbs and Western Medicine for New Wound Dressings Through Handheld Electrospinning. Biomedicines 2023, 11, 2146 - Jianfeng Zhou; Liangzhe Wang; Wenjian Gong; Bo Wang; Deng-Guang Yu; Yuanjie Zhu (Biomedicines)
In the original publication [...]